2020
DOI: 10.1016/bs.coac.2019.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Emerging halogenated flame retardants in the indoor environment

Abstract: Indoor environments are considered an important contributor to external human exposure to halogenated flame retardants (HFRs) due to the large amounts of chemicals currently incorporated in indoor equipment and the time humans spend every day in indoor environments. In this chapter, the presence and use of novel brominated flame retardants (NBFRs), dechlorane plus (DPs), chlorinated organophosphorus flame retardants (Cl-PFRs) and chlorinated paraffins (CPs) in indoor dust, air and consumer products collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 100 publications
(203 reference statements)
0
4
1
Order By: Relevance
“…Importantly, the ∑ CP (C 10-20 ) concentrations measured in this study were also one to three orders of magnitude higher than those of brominated and organophosphate flame retardants (BFRs and OPFRs, respectively) reported in indoor dust from Belgium (Van den Eede et al, 2011;Ali et al, 2011;D'Hollander et al, 2010;Roosens et al, 2009) and other studies, broadly (Poma et al, 2020). In Belgian house dust samples, the sum of nine OPFRs ranged 1.92 to 94.7 μg/g (median 13.3 μg/ g) (Van den Eede et al, 2011), decabromodiphenyl ether (BDE-209) ranged < 0.005 to 5.3 μg/g (median 0.31 μg/g), hexabromocyclododecanes (HBCDs) ranged 0.005 to 42.7 μg/g (median 0.13 μg/g) (D'Hollander et al, 2010) and the highest individual measurement among five novel BFRs was 5.0 μg/g of bis(2-ethylhexyl)-3,4,5,6-tetrabromophthalate (TBPH) (Ali et al, 2011).…”
Section: Concentrationscontrasting
confidence: 47%
See 2 more Smart Citations
“…Importantly, the ∑ CP (C 10-20 ) concentrations measured in this study were also one to three orders of magnitude higher than those of brominated and organophosphate flame retardants (BFRs and OPFRs, respectively) reported in indoor dust from Belgium (Van den Eede et al, 2011;Ali et al, 2011;D'Hollander et al, 2010;Roosens et al, 2009) and other studies, broadly (Poma et al, 2020). In Belgian house dust samples, the sum of nine OPFRs ranged 1.92 to 94.7 μg/g (median 13.3 μg/ g) (Van den Eede et al, 2011), decabromodiphenyl ether (BDE-209) ranged < 0.005 to 5.3 μg/g (median 0.31 μg/g), hexabromocyclododecanes (HBCDs) ranged 0.005 to 42.7 μg/g (median 0.13 μg/g) (D'Hollander et al, 2010) and the highest individual measurement among five novel BFRs was 5.0 μg/g of bis(2-ethylhexyl)-3,4,5,6-tetrabromophthalate (TBPH) (Ali et al, 2011).…”
Section: Concentrationscontrasting
confidence: 47%
“…It is important to note that exposure estimations reported here, based on the assumption of 100 % bioaccessibility of ingested CPs, will necessarily overestimate true internal uptake, with experimental evidence suggesting homologue specific bioaccessibility of dust borne SCCPs and MCCPs to range between 7.9 and 45.8 % (Du et al, 2021). Conversely, CP exposure via dust ingestion in the workplace and vehicles, where concentrations of similar compounds, such as flame retardants, have typically been higher than in homes (Poma et al, 2020;He et al, 2019;McGrath et al, 2022;McGrath et al, 2018), is not accounted for in the present study. The higher CP body burdens and associated increased health risks experienced by toddlers from ingestion of contaminated indoor dust results from the combined factors of smaller body weight and behaviours which accelerate ingestion of dust such as mouthing of toys and objects.…”
Section: Human Exposure Assessmentmentioning
confidence: 75%
See 1 more Smart Citation
“…Release of SCCPs via volatilization has been evidenced from PVC flooring during thermal treatment by Zhan et al [17] while SCCPs, MCCPs and LCCPs have been observed to migrate from other treated materials [9,15,18]. Such leaching from CP-treated products can lead to contamination of environmental matrices and indoor dust, resulting in human exposure [10,19,20]. For items such as toys or sporting equipment, exposure via direct dermal contact or mouthing by children and toddlers must also be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorinated paraffins (CPs), mostly composed of polychlorinated alkanes (PCAs), are a complex mixture of tens of thousands of individual compounds which have been used as plasticizers, flame retardants and lubricants in a wide variety of consumer goods and materials including polyvinyl chloride, rubber, adhesives, sealants and textiles. , Global production of PCAs has increased substantially during recent decades with recent total manufacture predicted to exceed one million tonnes per year as of 2020 . PCAs may be released from materials via volatilization, abrasion or direct transfer to other matrices and have been identified as one of the major plasticizer contaminants in indoor dust, resulting in human exposure via inadvertent dust ingestion. Commercial CP products are typically categorized by the most prominent carbon chain length of PCA constituents as short- (C 10–13 ), medium- (C 14–17 ), and long- (C ≥18 ) chain CPs (SCCPs, MCCPs and LCCPs, respectively) . SCCP, MCCP, and LCCP groups have each exhibited bioaccumulative and toxic endocrine disrupting properties and have been detected globally in human blood and breastmilk in numerous studies.…”
Section: Introductionmentioning
confidence: 99%